Does the random inspection reduce audit opinion shopping? - Guoqing Zhang; Sicen Chen; Pengdong Zhang; Xiaowei Lin (China Journal of Accounting Studies (CJAS), 2022)
The China Securities Regulatory Commission (CSRC) has randomly selected two audit firms each year to check their problems in management and internal control since 2016. Using the random inspections from 2016 to 2018, we construct a staggered DID model and find that the possibility of audit firms engaging in audit opinion shopping decreases after they are inspected. To explore the underlying logic, we document that: (1) the random inspections strengthened audit firms' management of branch offices, resulting in a more pronounced effect on the practice of branch audit offices; and (2) the policy improved audit firms' internal control, leading to more pronounced effect in audit firms with a heavy workload and loose control. Further, we show that punishments following the inspections strengthen the basic effect, while the effect of random inspections would be weakened for the big 10 audit firms.
Keywords: 650; Random inspection; audit opinion shopping; audit independence